Reconstruction of Islamic Religious Education Curriculum Responsive to Gender and Religious Moderation - Asykur, Muamar; Usman, Abdurrahim Supardi; Nurliana, Nurliana; Sari, Lilis Permata; Nurmiani, Nurmiani (International Journal on Advanced Science, Education, and Religion, 2025)
his study examines the reconstruction of the Islamic Education Curriculum (PAI) in Indonesia with a focus on gender responsiveness and religious moderation. Amidst increasing identity-based polarization and gender-based discrimination, there is a growing urgency for an inclusive and transformative educational framework. This study uses a qualitative-empirical method using literature studies, curriculum analysis, and interviews with PAI educators. The research findings reveal that the curriculum is still heavily biased towards doctrinal teaching with limited space for gender equality and pluralist discourse. This study proposes a conceptual model that integrates gender-sensitive pedagogy and wasathiyah (moderation) values ​​rooted in the principles of the Qur'an and national education goals. This reconstruction aims to foster critical awareness, tolerance, and social justice values ​​in students. The implications of this study support the revision of the national curriculum content, teacher training modules, and the development of inclusive learning models in PAI.